Microalgae cultivation in palm oil mill effluent for fuel feedstock production / Cheah Wai Yan - Cheah , Wai Yan (2019)
The sustainable use of petroleum-based fuel has been implicated as a major contributing factor for the greenhouse gas emissions, leading to climate change and global warming. The severe environmental impacts we are confronting today are resulted from fossil fuel consumption. Microalgae are the well-known feedstock for microalgal-based biofuel production. The microalgae cultivation of Chlorella sorokiniana CY-1 was carried out using palm oil mill effluent (POME) as cultivation medium for lipid production. POME is generated massively in Malaysia. The integration of using POME as microalgae cultivation medium not only allow biofuel production but also provide POME phycoremediation. The effectiveness of microalgae biomass growth and lipid accumulation in POME was investigated in the study. Enhancement strategies were carried out to enhance the microalgae biomass and lipid yields. The physico-chemical and biological approaches were applied, including wastewater pretreatment prior to microalgae cultivation, effective chemical supplementations, bacterial pretreatment and microalgae-bacteria co-cultivation. The most effective strategy was further studied on its scale up capability using novel photobioreactor. The results showed the CY-1 was able to be grown in 30% (v/v) POME medium. Acid pretreatment on POME though has enhanced biomass and lipid yields of CY-1 but the results was not satisfactory. Supplementations using glucose, urea and glycerol at 200 mg L-1 each performed best for biomass growth and lipid content of CY-1. Subsequent study continued for bacterial pretreatment and bacterial co-cultivation study using Pseudomonas species. Co-cultivation of CY-1 and Pseudomonas sp. at ratio of 1:1 exerted highest biomass yield of 2.04 g L-1 and lipid content of 16.04%. The last part of the study involved novel photobioreactor design at scale up level. Comparison was made between glass-made vessel photobioreactor and novel-design photobioreactor. The biomass concentration of CY-1 cultivated in novel-designed photobioreactor was excellent in performance, with 5.74 g L-1, which was 2.3 folds higher than the glass-made vessel photobioreactor. The lipid content exhibited was relatively satisfactory and comparable to smaller scale study, with 14.43%. Fatty acids compositions were dominated by C15 (52.67%), C18 (29.66%) and C16 (24.89%), which were the desirable fatty acids for biodiesel production. POME bioremediation attained were removal of COD (93.7%), TN (98.6%) and TP (96.0%). The cultivation using wastewater was also contributing to promote economic feasibility of commercial scale microalgae cultivation for biofuel production. The study relating to application of POME for microalgae cultivation and enhancement strategies are still scarce in Malaysia. Further studies ought to be carried out to advance the microalgal-based biofuel fields. This study is contributing in achieving cost-effective microalgae production for bioenergy, together with environmental sustainability.